Performance evaluation of asphalt binders modified with pyrolytic chars and WMA additive. (2022) - Kumar, Abhinay; Choudhary, Rajan; Kumar, Ankush
Abstract: Pyrolysis is a prominent waste-to-energy conversion process that allows for energy recovery and the creation of fuels from discarded/scrap tires and waste plastics. Tire and plastic pyrolytic chars (TPC and PPC) are solid fine carbonaceous materials released as by-products during the pyrolysis process. The application of TPC and PPC as asphalt binder modifier can yield beneficial effects on the rheological properties; however, mix preparation with TPC and PPC modified asphalt binders may require more energy due to their increased stiffness/viscosity. The introduction of warm mix asphalt (WMA) technology can help lower down the high production temperatures of the char-modified binders. This paper investigates the influence of a WMA additive on the production temperatures and dynamic mechanical properties of pyrolytic char modified binders. The production temperatures for binders were determined based on different rheological methods. Master curves were plotted from frequency sweep data. The rutting performance of the binders was determined through multiple stress creep and recovery (MSCR) tests. The MSCR data was also modelled using Burgers four-element model. Linear amplitude sweep (LAS) tests were used to evaluate the binder fatigue resistance. The incorporation of WMA additive effectively reduced the production temperatures of char-modified binders. The resistance to rutting and fatigue cracking was also enhanced after the addition of the WMA additive. Overall, the findings indicate that pyrolytic char-WMA composite modified asphalt binders have a good potential for use in road pavements.